Advances in CAR optimization strategies based on CD28 - Li, Sijin; Zhou, Yusi; Wang, Hairong; Qu, Gexi; Zhao, Xuan; Wang, Xu; Hou, Rui; Guan, Zhangchun; Liu, Dan; Zheng, Junnian; Shi, Ming (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR)-T cell therapy, which utilizes genetic engineering techniques to modify T-cells to achieve specific targeting of cancer cells, has made significant breakthroughs in cancer treatment in recent years. All marketed CAR-T products are second-generation CAR-T cells containing co-stimulatory structural domains, and co-stimulatory molecules are critical for CAR-T cell activation and function. Although CD28-based co-stimulatory molecules have demonstrated potent cytotoxicity in the clinical application of CAR-T cells, they still suffer from high post-treatment relapse rates, poor efficacy durability, and accompanying severe adverse reactions. In recent years, researchers have achieved specific results in enhancing the anti-tumor function of CD28 by mutating its signaling motifs, combining the co-stimulatory structural domains, and modifying other CAR components besides co-stimulation. This paper reviewed the characteristics and roles of CD28 in CAR-T cell-mediated anti-tumor signaling and activation. We explored potential strategies to enhance CAR-T cell efficacy and reduce side effects by optimizing CD28 motifs and CAR structures, aiming to provide a theoretical basis for further clinical CAR-T cell therapy development.